Current human capital requirement of aircraft engineering in Malaysia - Wan Zaidi, Wan Omar; Shuhaimi, Mansor, Ir. Assoc. Prof. Dr. (The Institution of Engineers, Malaysia, 2011)
Link to publisher’s home page at http://www.myiem.org.my/